Complex Neurological Phenotype Associated with a De Novo DHDDS Mutation in a Boy with Intellectual Disability, Refractory Epilepsy, and Movement Disorder - Piccolo, Gianluca; Amadori, Elisabetta; Vari, Maria Stella; Marchese, Francesca; Riva, Antonella; Ghirotto, Valentina; Iacomino, Michele; Salpietro, Vincenzo; Zara, Federico; Striano, Pasquale (Journal of Pediatric Genetics, 2020)
Mutations in the DHDDS gene (MIM: 617836), encoding a subunit of dehydrodolichyl diphosphate synthase complex, have been recently implicated in very rare neurodevelopmental diseases. In total, five individuals carrying two de novo mutations in DHDDS have been reported so far, but genotype–phenotype correlations remain elusive. We reported a boy with a de novo mutation in DHDDS (NM_205861.3: c.G632A; p.Arg211Gln) featuring a complex neurological phenotype, including mild intellectual disability, impaired speech, complex hyperkinetic movements, and refractory epilepsy. We defined the electroclinical and movement disorder phenotype associated with the monoallelic form of the DHDDS-related neurodevelopmental disease and possible underlying dominant-negative mechanisms.
Keywords: DHDDS; neurodevelopmental disorder; epilepsy